Data-driven analysis for source apportionment and geochemical backgrounds establishment of toxic elements and REEs in the Tohoku region, Japan. (January 2021) - Pujiwati, Arie; Wang, Jiajie; Nakamura, Kengo; Kawabe, Yoshishige; Watanabe, Noriaki; Komai, Takeshi
Abstract: The Tohoku region of Japan is geologically diverse, with a long agriculture and mining history; however, little information about the origins and distribution mechanisms of elements in this region has been reported. This study aims to provide fundamental insights into the effects of geological features and anthropogenic activities on various elements, including toxic elements and rare-earth elements (REEs), in the Tohoku region. A geochemical database (2007, AIST) consisting of data for 53 elements in 485 river sediment samples from the region was used, and a data-driven method combining principal component analysis (PCA) was applied for analysis. GBs for numerous types of areas, including general areas (GGB), natural environments (NGB), high anthropogenic-influenced areas (AGB) and mineralised areas (MGB) were established; especially, MGB was newly proposed in this study to illuminate the role of ore deposits. Both PCA and GBs comparison results show that geological features (especially igneous rock distribution) were the most important factor affecting elemental distribution, rather than anthropogenic activities. In the PCA, the first principal component showed that REE resources were commonly associated with the distribution of granitic rocks and REE-bearing minerals. Anthropogenic contaminations from mining, urban, and anthropogenic areas played important roles as the origin of some toxic elements (e.g. Ni, Pb, Sb). Comparisons between these GBs effectively elucidated the enrichment of certain toxic elements (e.g., Hg, Sb) in ore deposit areas. This data-driven study not only clarified the origins of toxic elements, but also revealed the location of potential REE mineral resources in the Tohoku region. Highlights: Numerous GBs of Tohoku region were established based on geochemical information. Elements origins and distribution were studied through data-driven PCA and GBs. Geological features highly influence both REEs and toxic elements distributions. Ore deposit and mining activities contributed to certain toxic elements enrichment.